Perovskite thin film and preparation method thereof, perovskite solar cell and preparation method thereof, and electric equipment
By alternately setting the inorganic salt and organic salt vapor deposition layers to form a sandwich structure, the problem of incomplete conversion of inorganic salts and mismatch of interface energy levels in perovskite films is solved, and the performance and production efficiency of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202411374386.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The inorganic salts in perovskite films cannot be completely converted into perovskites, resulting in the problem of increased internal resistance and mismatch in interface energy levels.
The inorganic salt vapor deposition layer and the organic salt vapor deposition layer are alternately arranged by cyclic alternatingly to form a sandwich structure and the thickness of each layer is regulated to achieve complete conversion of perovskites and optimal matching of interface energy levels.
The high electrical conversion efficiency, stability and low cost of perovskite films are achieved, and the photoelectric conversion efficiency and production efficiency of perovskite solar cells are improved.
Smart Images

Figure CN119255690A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite film and a preparation method thereof, a perovskite solar cell and a preparation method thereof, and electrical equipment. Background Art
[0002] Perovskite materials have high electrical conversion efficiency. The solution method has problems such as uncontrollable film pinholes and poor reproducibility in the preparation of perovskite batteries, which makes it difficult to apply them on a large scale. The vacuum evaporation method has the advantages of no solvent, little environmental pollution, high film density, high production efficiency, and large-area continuous preparation, and has broad application prospects.
[0003] The conversion rate of perovskite crystals is an important factor affecting the quality of perovskite films and perovskite cells. However, since organic salts easily react with the surface of inorganic salts to form a dense perovskite surface layer, which prevents the diffusion of organic salts, inorganic salts far away from the organic salt layer cannot be completely converted into perovskites. In addition, the diffusion distance of solid organic salts is short, which easily makes the composition of perovskite films uneven, resulting in increased internal resistance of perovskite films and mismatch of interface energy levels between the perovskite layer and the upper and lower functional layers.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a perovskite film to solve the problems in the prior art that inorganic salts such as lead salts in the perovskite film cannot be completely converted into perovskites, and the non-uniform composition of the perovskite film leads to an increase in the internal resistance of the perovskite film, and the mismatch of the interface energy levels between the perovskite layer and the upper and lower functional layers. Specifically, the perovskite film includes an inorganic salt vapor deposition layer and an organic salt vapor deposition layer that are alternately stacked in a cycle; wherein the inorganic salt vapor deposition layer includes at least three layers, and the organic salt vapor deposition layer includes at least two layers; the thickness of each inorganic salt vapor deposition layer is 10 to 300 nm; the thickness of each organic salt vapor deposition layer is 10 to 400 nm. The present invention arranges inorganic salt evaporation layers and organic salt evaporation layers that are alternately stacked in a cycle, so that the inorganic salt evaporation layers and the organic salt evaporation layers are stacked in a sandwich manner, and the thickness of each inorganic salt evaporation layer and the organic salt evaporation layer is regulated so that the organic salt can diffuse in the inorganic salt layer, and the complete conversion of perovskite can be achieved, thus solving the problem that inorganic salts such as lead salts in traditional perovskite films cannot be completely converted into perovskites, and the problem that the non-uniform composition of the perovskite film leads to an increase in the internal resistance of the perovskite film. The general formula of the perovskite film is FA 1-y-z Cs y MA z PbI 3- x Br x, wherein 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, 0≤y+z≤0.5. The present invention controls the chemical composition of the perovskite film, controls the ratio of organic salt to inorganic salt, and then regulates the various element components in the perovskite layer, thereby achieving the optimal matching of the perovskite interface energy level, and solves the problem of mismatch between the interface energy levels of the perovskite layer and the upper and lower functional layers in the prior art.
[0006] The second object of the present invention is to provide a method for preparing a perovskite film according to FA 1-y-z Cs y MA z PbI 3- x Br x , 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, 0≤y+z≤0.5, and sequentially cyclically evaporating an inorganic salt material and an organic salt material on the bottom surface, wherein at least three layers of the inorganic salt material are evaporated, and at least two layers of the organic salt material are evaporated, and then annealing is performed; the inorganic salt material is selected from at least one of PbI2, PbBr2, CsI and CsBr, and the organic salt material is selected from at least one of FABr, FAI, MABr and MAI, and the inorganic salt material contains a Pb element, the organic salt material contains a FA group, and the inorganic salt material and / or the organic salt material contains an I element. The present invention controls the ratio of organic salt to inorganic salt and regulates the various element components in the perovskite film to achieve the optimal matching of the perovskite interface energy level. The perovskite film is prepared by cyclically evaporating an inorganic salt material and an organic salt material in sequence, so that the inorganic salt evaporation layer and the organic salt evaporation layer are stacked in a sandwich manner, and the complete conversion of the perovskite can be achieved. In addition, the evaporation method greatly improves the production efficiency of perovskite films, can realize the preparation of high-quality large-size perovskite films, and achieve the controllable composition, thickness and uniformity of perovskite films.
[0007] The third object of the present invention is to provide a perovskite solar cell, which comprises the above-mentioned perovskite film, or a perovskite film prepared according to the above-mentioned method for preparing the perovskite film. The above-mentioned perovskite solar cell has the advantages of high photoelectric conversion efficiency, good stability, low cost, high yield and high production efficiency.
[0008] The fourth object of the present invention is to provide a method for preparing the above-mentioned perovskite solar cell, which specifically includes the following steps: using a full dry method, that is, using a dry process without a wet process, to form each functional layer on a substrate to obtain a perovskite solar cell. Wherein, the functional layer at least includes the above perovskite film. The dry process of the full dry method at least includes an evaporation method. The above-mentioned preparation method has the advantages of low environmental pollution, high film density, high production efficiency, and large-area continuous preparation.
[0009] The fifth object of the present invention is to provide an electrical device, which at least includes the above-mentioned perovskite solar cell. In other words, the above-mentioned electrical device refers to any equipment, system or device containing the above-mentioned perovskite solar cell, such as a lighting system, a mobile communication device, a portable product, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1 A schematic diagram of the structure of the perovskite film provided by the present invention;
[0012] Figure 2 This is a SEM cross-sectional view of the perovskite film obtained in Example 1 provided by the present invention;
[0013] Figure 3 This is a SEM surface morphology image of the perovskite film prepared in Example 1 provided by the present invention. DETAILED DESCRIPTION
[0014] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0015] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0016] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or may only include or comprise the listed components.
[0017] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0018] In a first aspect, the present invention provides a perovskite film, which comprises an inorganic salt vapor deposition layer and an organic salt vapor deposition layer which are sequentially and cyclically alternately stacked. That is, the inorganic salt vapor deposition layer and the organic salt vapor deposition layer are stacked and cyclically alternately stacked.
[0019] Furthermore, the number of the inorganic salt vapor-deposited layers includes at least three layers, for example, four layers, five layers, six layers, seven layers, eight layers, nine layers, ten layers or more.
[0020] Furthermore, the number of organic salt vapor-deposition layers includes at least two layers, for example, three layers, four layers, five layers, six layers, seven layers, eight layers, nine layers, ten layers or more.
[0021] Among them, the inorganic salt vapor deposition layer includes at least three layers, and the organic salt vapor deposition layer includes at least two layers, which means that the perovskite film at least includes an inorganic salt vapor deposition layer, an organic salt vapor deposition layer, an inorganic salt vapor deposition layer, an organic salt vapor deposition layer and an inorganic salt vapor deposition layer stacked in sequence, and each layer forms a sandwich structure, see Figure 1 shown.
[0022] However, the perovskite film can also have other structures, for example, including an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, and an organic salt vapor-deposited layer stacked in sequence, or an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, or an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, an organic salt vapor-deposited layer, an inorganic salt vapor-deposited layer, and an organic salt vapor-deposited layer stacked in sequence.
[0023] Further, the thickness of each inorganic salt vapor-deposited layer, or the thickness of a single layer of the inorganic salt vapor-deposited layer, is 10 to 300 nm, including but not limited to any point value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 270 nm, 300 nm or any range value between two of them. The thickness of a single layer of inorganic salt vapor-deposited layer is within this range, which is not only convenient for controlling its thickness, but also conducive to the formation of perovskite.
[0024] Further, the thickness of each organic salt vapor-deposited layer, or the thickness of a single layer of the organic salt vapor-deposited layer, is 10 to 400 nm, including but not limited to any point value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, or any range value between two of them. The thickness of a single layer of organic salt vapor-deposited layer within this range is beneficial to the control of its thickness on the one hand, and is beneficial to the diffusion of organic salt molecules in the inorganic salt layer on the other hand, promoting the formation of perovskite.
[0025] In order to solve the problem that inorganic salts such as lead salts in the perovskite film of the prior art cannot be completely converted into perovskite, and the internal resistance of the perovskite film increases due to the uneven composition of the perovskite film, the present invention provides a perovskite film, which is provided with an inorganic salt vapor-deposited layer and an organic salt vapor-deposited layer which are sequentially and cyclically alternately stacked, so that the inorganic salt vapor-deposited layer and the organic salt vapor-deposited layer are stacked in a sandwich manner, and the thickness of each layer of the inorganic salt vapor-deposited layer and the organic salt vapor-deposited layer is regulated so that the organic salt molecules can diffuse in the inorganic salt layer, thereby achieving complete conversion of the perovskite.
[0026] Furthermore, the general formula of the perovskite film is FA 1-y-z Cs y MA z PbI 3-x Br x, where 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, and 0≤y+z≤0.5. Where x includes but is not limited to any point value of 0, 0.01, 0.05, 0.1, 0.3, 0.5, 0.8, 1, 1.2, 1.3, and 1.5, or any range value between two of them; y includes but is not limited to any point value of 0, 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, and 0.5, or any range value between two of them; z includes but is not limited to 0, The point values of any one of 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or the range values between any two thereof; y+z includes but is not limited to the point values of any one of 0, 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or the range values between any two thereof.
[0027] In order to solve the problem of mismatch between the interface energy levels of the perovskite layer and the upper and lower functional layers in the prior art, the present invention further controls the chemical composition of the perovskite film, controls the ratio of organic salt to inorganic salt, and then regulates the various element components in the perovskite layer, so as to achieve optimal matching of the perovskite interface energy levels and obtain a high-efficiency perovskite film and perovskite solar cell.
[0028] Therefore, the perovskite film provided by the present invention has high electrical conversion efficiency.
[0029] In addition, the perovskite film composed of a vapor-deposited layer also has the advantages of high density and low environmental pollution.
[0030] In some specific embodiments, in order to further improve the photoelectric conversion efficiency of the perovskite film and the perovskite solar cell obtained therefrom, the thickness of each layer of the inorganic salt vapor-deposited layer is preferably 20 to 200 nm, including but not limited to any point value of 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, and 200 nm or a range value between any two of them.
[0031] In some specific embodiments, in order to further improve the photoelectric conversion efficiency of the perovskite film and the perovskite solar cell obtained therefrom, the thickness of each organic salt vapor-deposited layer is preferably 20 to 400 nm, including but not limited to any point value of 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, and 400 nm, or a range value between any two of them.
[0032] In some specific embodiments, in order to improve the conversion rate of perovskite and improve the photoelectric conversion efficiency of the perovskite film and the perovskite solar cell made therefrom, in two adjacent layers, the ratio of the single layer thickness of the inorganic salt evaporated layer to the single layer thickness of the organic salt evaporated layer is 0.1 to 5:1, including but not limited to any point value of 0.1:1, 0.2:1, 0.3:1, 0.5:1, 0.8:1, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, and 5:1, or a range value between any two of them. It is understandable that the thickness of each inorganic salt vapor-deposited layer may be the same or different, and the thickness of each organic salt vapor-deposited layer may be the same or different.
[0033] In some specific embodiments, the sum of the thicknesses of the inorganic salt deposited layers, that is, the total thickness of all inorganic salt deposited layers, is 60 to 500 nm, including but not limited to any point value of 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, and 500 nm, or a range value between any two of them. This is beneficial to improving the conversion rate of perovskite crystals and the photoelectric conversion efficiency of the perovskite solar cells obtained therefrom.
[0034] In some specific embodiments, in order to further improve the conversion rate of perovskite, the organic salt evaporation layer includes at least five layers, including but not limited to any point value of five layers, six layers, seven layers, eight layers, nine layers, and ten layers, or a range value between any two of them.
[0035] In some specific embodiments, in order to further improve the conversion rate of perovskite, the inorganic salt evaporation layer includes at least four layers, including but not limited to any one of four layers, five layers, six layers, seven layers, eight layers, nine layers, ten layers, eleven layers, and twelve layers, or a range value between any two of them.
[0036] In some specific implementations, 0≤x≤1, which is beneficial to further improve the conversion rate of perovskite and the photoelectric conversion rate of the battery made therefrom.
[0037] In some specific implementations, 0≤y≤0.2, which is beneficial to further improve the conversion rate of perovskite and the photoelectric conversion rate of the battery prepared therefrom.
[0038] In some specific implementations, 0.1≤z≤0.2, which is beneficial to further improve the conversion rate of perovskite and the photoelectric conversion rate of the battery prepared therefrom.
[0039] In some specific implementations, 0.1≤y+z≤0.4, which is beneficial to further improve the conversion rate of perovskite and the photoelectric conversion rate of the battery prepared therefrom.
[0040] In some specific embodiments, the chemical formula of the perovskite film includes FA 0.9 MA 0.1 PbI2Br、FA 0.8 Cs 0.1 MA 0.1 PbI2Br、FA 0.8 Cs 0.1 MA 0.1 PbI 2.5 Br 0.5 , FA 0.7 Cs 0.1 MA 0.2 PbI 2.5 Br 0.5 , FA 0.7 Cs 0.1 MA 0.2 PbI2Br and FA 0.9 MA 0.1 PbI3.
[0041] In some specific embodiments, the perovskite film includes an inorganic salt evaporation layer, an organic salt evaporation layer, an inorganic salt evaporation layer, an organic salt evaporation layer, an inorganic salt evaporation layer, an organic salt evaporation layer, an inorganic salt evaporation layer, an organic salt evaporation layer, and an inorganic salt evaporation layer stacked in sequence. That is, the total number of layers of the perovskite film is 9 layers. The total number of layers of the inorganic salt evaporation layer is 5 layers, and the total number of layers of the organic salt evaporation layer is 4 layers. The thickness of each inorganic salt evaporation layer may be the same or different. The thickness of each organic salt evaporation layer may be the same or different. The sum of the thicknesses of the various inorganic salt evaporation layers is 300nm. This is conducive to achieving complete conversion of perovskite and improving the quality of the perovskite film and its electrical conversion efficiency.
[0042] In a second aspect, the present invention provides a method for preparing the above-mentioned perovskite film, the preparation method comprising the following steps: according to the following chemical formula: FA 1-y-z Cs y MA z PbI 3-x Br x , wherein 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, 0≤y+z≤0.5, weigh or obtain inorganic salt material and organic salt material.
[0043] Among them, the inorganic salt material is selected from at least one of PbI2, PbBr2, CsI and CsBr, the organic salt material is selected from at least one of FABr, FAI, MABr and MAI, and the inorganic salt material must contain Pb element, the organic salt material must contain FA group, and the inorganic salt material and / or organic salt material contains I element.
[0044] Then, a bottom layer is prepared, and an inorganic salt material and an organic salt material are sequentially and cyclically deposited on the surface of the bottom layer, that is, the inorganic salt material and the organic salt material are alternately and cyclically deposited, wherein the inorganic salt material is the first layer to be deposited.
[0045] During the evaporation process, at least three layers of inorganic salt material are evaporated, and at least two layers of organic salt material are evaporated. After the evaporation is completed, annealing treatment is performed and then cooling is performed to obtain a perovskite film.
[0046] It can be understood that the evaporation area × evaporation thickness = coating volume, coating volume × coating density (raw material density) = coating weight. Among them, the evaporation area is a certain value, which can be measured and controlled. By monitoring the temperature and rate of evaporation through the crystal oscillator probe and the film thickness controller, and setting the deposition time, the evaporation thickness can be accurately controlled. According to the target chemical formula, the molar ratio of each element and the weight ratio of each raw material required can be calculated, and then the density of the coating can be obtained. In the evaporation process, the raw materials used are in excess, but the evaporation thickness is controllable. By controlling the evaporation thickness, the weight of a single layer of coating can be obtained, and then the number of layers can be coordinated to obtain the final perovskite film corresponding to the target chemical formula.
[0047] The method for preparing a perovskite film provided by the present invention prepares the perovskite film by cyclic sequential evaporation, so that the inorganic salt evaporation layer and the organic salt evaporation layer are stacked in a sandwich manner, and the complete conversion of the perovskite can be achieved.
[0048] At the same time, the evaporation method greatly improves the production efficiency of perovskite films, increases the conversion rate of perovskites, achieves controllable composition, thickness and uniformity of perovskite films, realizes continuous and large-scale production, and realizes energy level regulation of perovskite battery interfaces.
[0049] In addition, the evaporation method also solves the shortcomings of the solution method for preparing perovskite films, such as long production time, few types of applicable substrates, many defects in large-area preparation, low yield, and uneven perovskite films.
[0050] In addition, the preparation method of the perovskite film provided by the present invention can achieve optimal matching of the perovskite interface energy levels by controlling the ratio of organic salt to inorganic salt and regulating the various element components in the perovskite film, thereby obtaining a high-efficiency perovskite film and a perovskite solar cell.
[0051] In some specific embodiments, the method of evaporating the inorganic salt material includes but is not limited to: a preheating method. The preheating method does not need to be performed in steps, has a higher timeliness, and has a fast evaporation rate, and is conducive to the precise control of the evaporation process, thereby improving the uniformity and yield of the perovskite film.
[0052] In some specific embodiments, the steps of evaporation by preheating method are as follows: weigh each raw material according to the target chemical formula ratio, place it in a crucible, and then -3 Pa~1×10 -5 Pa vacuum, preheat at 300-500°C, and after preheating for 10-60 minutes, heat and evaporate. The inorganic salt raw materials can be molten salt crystals or powders. The vacuum degree includes but is not limited to 1×10 -3 Pa, 1×10 -4Pa, 5×10 -4 Pa, 1×10 -5 Pa or any range between them; the preheating temperature includes but is not limited to 300°C, 310°C, 320°C, 330°C, 350°C, 380°C, 400°C, 430°C, 450°C, 480°C, 500°C or any range between them; the preheating time includes but is not limited to 10min, 20min, 30min, 40min, 50min, 60min or any range between them. The above method can promote the transformation of perovskite crystals, improve the uniformity and yield of perovskite films, and is conducive to the regulation of the thickness of perovskite films.
[0053] In some specific implementations, the method of evaporating the inorganic salt material includes but is not limited to the single crystal method. The single crystal method can store materials and has the advantages of simple process, low cost, and convenient operation.
[0054] In some specific implementations, the steps of evaporation using the single crystal method are as follows: the raw materials are mixed evenly according to the target chemical formula ratio, and then a single crystal material is prepared by melting, and then the single crystal material is used as a material for heating and evaporation. This method can store materials, has a simple process, low operating difficulty, low cost, and is suitable for large-scale production.
[0055] In some specific embodiments, the method for evaporating the organic salt material includes the following steps: mixing the raw materials in a target chemical formula ratio, and then heating and evaporating; or, heating the raw materials separately, mixing and evaporating. The evaporation temperature of this method is low, and evaporation can be performed after mixing evenly, or different sources can be controlled separately to achieve mixed evaporation, which has the advantages of simple process, low cost, and suitability for mass production.
[0056] In some specific embodiments, when the inorganic salt material is evaporated, the vacuum degree of the evaporation is ≤1×10 -3 Pa; but not limited to 1×10 -3 Pa, 1×10 -4 Pa, 3×10 -4 Pa, 5×10 -4 Pa, 8×10 -4 Pa, 1×10 -5 Any point value of Pa or any range value between them. The vacuum degree of evaporation affects the performance, firmness, purity and crystallization of the coating. The quality and performance of perovskite films can be improved by using this vacuum degree.
[0057] In some specific embodiments, when the inorganic salt material is evaporated, the evaporation rate of the evaporation is Including but not limited to Any point value of or any range value between the two. The evaporation rate will significantly affect the evaporation effect. The evaporation rate can improve the uniformity and density of the coating, thereby obtaining a high-quality perovskite film.
[0058] In some specific embodiments, when the inorganic salt material is evaporated, the rotation speed of the substrate stage of the evaporation equipment used is 3 to 20 r / min, including but not limited to any point value of 3 r / min, 4 r / min, 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min, 10 r / min, 12 r / min, 15 r / min, 18 r / min, and 20 r / min or any range value between two of them. The rotation speed of the substrate stage of the evaporation equipment will affect the uniformity and production efficiency of the film. The use of this rotation speed is conducive to improving the quality of the perovskite film and improving the production efficiency.
[0059] In some specific embodiments, when the organic salt material is evaporated, the vacuum degree of the evaporation is ≤1×10 -2 Pa, including but not limited to 1×10 -2 Pa, 1×10 -3 Pa, 1×10 -4 Pa, 3×10 -4 Pa, 5×10 -4 Pa, 8×10 -4 Pa, 1×10 -5 Any point value of Pa or any range value between two of them. The use of this vacuum degree is beneficial to improving the quality and performance of the perovskite film.
[0060] In some specific embodiments, when the organic salt material is evaporated, the evaporation rate of the evaporation is Including but not limited to The evaporation rate can improve the uniformity and density of the film, which is beneficial to improving the quality of the perovskite film and its conversion efficiency.
[0061] In some specific embodiments, when the organic salt material is evaporated, the rotation speed of the substrate stage of the evaporation equipment used is 3 to 20 r / min, including but not limited to any point value of 3 r / min, 4 r / min, 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min, 10 r / min, 12 r / min, 15 r / min, 18 r / min, and 20 r / min or any range value between two of them. The use of this rotation speed is conducive to improving the uniformity of the perovskite film and its conversion efficiency, and improving production efficiency.
[0062] In some specific embodiments, the annealing temperature is 1000-2000°C, including but not limited to any one of 1000°C, 1200°C, 1300°C, 1500°C, 1800°C, 2000°C or a range between any two of them.
[0063] In some specific embodiments, the holding time of the annealing treatment is 10 to 60 minutes, including but not limited to any one of 10 minutes, 20 minutes, 30 minutes, and 60 minutes, or a range between any two of them. This holding time is beneficial to further improve the quality of the perovskite film and its photoelectric conversion efficiency.
[0064] Annealing temperature and holding time will affect the crystal structure, quality, and final photovoltaic performance of the film. Annealing is a key step in the preparation of perovskite films, which has a direct impact on the crystal structure and quality of the film. Appropriate annealing temperature and time can not only optimize the grain size and morphology of the perovskite film, but also ensure that the perovskite film forms a high-quality crystal structure, thereby improving the quality of the film. It can also reduce non-radiative trap density recombination, extend carrier lifetime, and thus improve the efficiency of photovoltaic cells. The temperature of this annealing treatment can improve the quality of the perovskite film and its photoelectric conversion efficiency.
[0065] In some specific embodiments, the bottom layer includes a substrate, and an electron transport layer disposed on a surface of the substrate.
[0066] In some specific embodiments, the bottom layer includes a substrate, and an electron transport layer and an inorganic salt passivation layer sequentially stacked on the surface of the substrate.
[0067] In some specific embodiments, the bottom layer includes a substrate, and a hole transport layer disposed on a surface of the substrate.
[0068] In some specific embodiments, the bottom layer includes a substrate, and a hole transport layer and an organic salt passivation layer sequentially stacked on the surface of the substrate. In a third aspect, the present invention provides a perovskite solar cell, which includes the above-mentioned perovskite film, or a perovskite film prepared according to the above-mentioned perovskite film preparation method.
[0069] The perovskite solar cell has high photoelectric conversion efficiency, good stability, low cost, high yield and high production efficiency.
[0070] In some specific embodiments, the perovskite solar cell includes, but is not limited to, one or more of a perovskite single cell, a perovskite stacked cell, a perovskite regular cell, and a perovskite transverse cell.
[0071] The perovskite solar cell provided by the present invention can be easily upgraded to develop stacked cells based on the existing bottom cell equipment, and has broad application prospects.
[0072] Specifically, the perovskite film provided by the present invention is not only suitable for small-area laboratory devices, but also can be used to prepare large-area perovskite single-cell batteries and perovskite stacked batteries, which provides a new option for the research and development and industrial preparation of perovskites.
[0073] In some specific embodiments, the perovskite solar cell includes a substrate, and a hole transport layer, an organic salt passivation layer, the perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer sequentially stacked on the surface of the substrate, which is a perovskite trans-cell. That is, in addition to the perovskite film provided by the present invention, the perovskite trans-cell may also include any one or more of a hole transport layer, an organic salt passivation layer, an inorganic salt passivation layer, an electron transport layer and an electrode layer. The present invention can improve the photoelectric conversion efficiency of the perovskite trans-cell and improve the stability of the perovskite solar cell by arranging each functional layer.
[0074] In some specific embodiments, the hole transport layer includes but is not limited to at least one of nickel oxide, cuprous thiocyanate and oligomeric PACz (phosphoric acid carbazole), for example, nickel oxide and oligomeric PACz are used, but not limited thereto. The hole transport layer mainly collects and transports holes to achieve effective separation of electrons and holes, while protecting the perovskite layer from erosion by oxygen and water vapor, thereby improving the efficiency and stability of the battery.
[0075] In some specific embodiments, the thickness of the hole transport layer is 10-100 nm, including but not limited to any point value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm or any range value between two thereof. The efficiency of the battery can be further improved by controlling the thickness of the hole transport layer.
[0076] In some specific embodiments, the organic salt passivation layer includes any one or more of tetrabutylammonium bromide, tetrabutylammonium iodide, methylammonium bromide, methylammonium chloride, ethylammonium chloride, phenethylammonium iodide, p-fluorophenethylammonium iodide, methylammonium iodide, phenethylammonium chloride, phenethylammonium bromide, tetra-tert-butylphenylammonium chloride, butylammonium bromide, isopropylammonium bromide, octylammonium iodide, benzylammonium chloride, tetrafluorobenzylammonium iodide, phenylpropylammonium iodide and tetrafluorophenethylammonium bromide.
[0077] The present invention provides an organic salt passivation layer to passivate defects between interface layers.
[0078] In some specific embodiments, the thickness of the organic salt passivation layer is 1-5 nm, including but not limited to any point value of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm or a range value between any two of them.
[0079] In some specific embodiments, the inorganic salt passivation layer includes but is not limited to LiF, ie, lithium fluoride.
[0080] The present invention sets a specific inorganic salt passivation layer, which interacts with the surface of the perovskite film, can effectively fill the grain boundary defects on the perovskite surface, reduce the surface roughness, optimize the surface morphology, thereby reducing the recombination of carriers at the interface and enhancing the transmission of carriers. This can not only improve the energy conversion efficiency of the device, but also significantly improve the stability of the device.
[0081] In some specific embodiments, the thickness of the inorganic salt passivation layer is 1-5 nm, including but not limited to any point value of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm or a range value between any two of them.
[0082] In some specific embodiments, the electron transport layer includes any one or more of titanium dioxide, zinc oxide, C60 and tin oxide. The electron transport layer is provided in the present invention, and its functions mainly include enhancing battery stability, optimizing interface energy level matching, and reducing interface resistance.
[0083] In some specific embodiments, the thickness of the electron transport layer is 10 to 100 nm, including but not limited to any point value of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, and 100 nm, or a range value between any two of them.
[0084] In some specific embodiments, the electrode layer includes at least one of copper (elemental copper) and silver (elemental silver). The electrode layer can collect and transport photogenerated charges, and is an important component of the battery.
[0085] In some specific embodiments, the thickness of the electrode layer is 50 to 200 nm, including but not limited to any point value of 150 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 170 nm, and 200 nm or a range value between any two of them.
[0086] In a fourth aspect, the present invention provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps: using a fully dry method, wherein the fully dry method refers to using a dry process without a wet process, to form various functional layers on a substrate to obtain a perovskite solar cell. The functional layer at least includes the above-mentioned perovskite film. The dry process of the fully dry method at least includes an evaporation method.
[0087] The fully dry method for producing perovskite solar cells has the advantages of low environmental pollution, high film density, high production efficiency, and large-area continuous preparation. It can solve the problems of high requirements for the base layer, many defects in large-area preparation, low yield, and uneven perovskite film produced in the traditional solution method (i.e. wet method) for preparing perovskite films.
[0088] In some specific embodiments, the functional layer further includes at least one of a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer.
[0089] In some specific implementations, the dry process of the full dry method further includes any one or both of a sputtering method and an atomic deposition method. The use of the full dry method to prepare each layer can improve the photoelectric conversion efficiency and stability.
[0090] In some specific embodiments, a fully dry method is used to prepare a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer, wherein the hole transport layer, the organic salt passivation layer, the perovskite film, the inorganic salt passivation layer, the electron transport layer and the electrode layer are collectively referred to as functional layers, that is, each functional layer is prepared by any one or more of evaporation, sputtering and atomic deposition methods.
[0091] In some specific embodiments, a hole transport layer having excellent hole extraction capability and energy band matching is prepared by evaporation and / or sputtering.
[0092] In some specific embodiments, the electron transport layer having excellent electron extraction capability and energy band matching is prepared by at least one of atomic deposition, evaporation and sputtering.
[0093] In some specific embodiments, the electrode layer is prepared by evaporation and / or magnetron sputtering to draw out the current.
[0094] In some specific embodiments, the substrate includes, but is not limited to, conductive glass.
[0095] In some specific embodiments, before forming each functional layer, the substrate is first cleaned. The cleaning method includes at least one of plasma cleaning and ultraviolet cleaning. Cleaning can remove pollutants, prevent pollution, improve charge transfer efficiency, and improve film formation effect.
[0096] In a fifth aspect, the present invention provides an electrical device, comprising the above-mentioned perovskite solar cell, or a perovskite solar cell prepared according to the above-mentioned perovskite solar cell preparation method.
[0097] The perovskite solar cell provided by the present invention can be widely used in various fields, wherein the electrical equipment includes any device, equipment and system containing the perovskite solar cell provided by the present invention, such as solar power system, photovoltaic building integration, lighting system, aerospace equipment, Internet of Things system, mobile power supply, vehicle, and mobile communication equipment, etc., and the present invention does not limit this.
[0098] More specifically, electrical equipment includes but is not limited to seat charging equipment, billboards, landscape lighting, building curtain walls, integrated photovoltaics, portable products, wearable electronic products, ground power stations, and wearable power generation devices.
[0099] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0100] The perovskite solar cell provided by the present invention can be any one of a single perovskite cell, a stacked perovskite cell, a regular perovskite cell and a trans perovskite cell. The preparation process of the trans perovskite cell is described in detail below by taking the example of the preparation process of the trans perovskite cell.
[0101] Example 1
[0102] The method for preparing a perovskite solar cell provided in this embodiment comprises the following steps:
[0103] (1) Bottom layer cleaning: Place the bottom layer of the conductive glass in a cleaning machine for UV cleaning.
[0104] (2) Preparation of hole transport layer: On the cleaned conductive glass substrate, a hole transport layer with excellent hole extraction ability and energy band matching is prepared by evaporation. The material of the hole transport layer is cuprous thiocyanate. The thickness of the hole transport layer is 20 nm.
[0105] (3) Preparation of organic salt passivation layer: On the surface of the hole transport layer, an organic salt passivation layer is prepared by evaporation, and the organic salt material used is tetrabutylammonium bromide. The thickness of the organic salt passivation layer is 3 nm.
[0106] (4) Preparation of perovskite film: On the surface of the organic salt passivation layer, a 1×10 -3 Under a vacuum degree of 1.5 Pa, PbI2 powder, PbBr2 powder, and CsI powder were placed in a crucible with a weight ratio of PbI2:PbBr2:CsI=5.02:7.06:1, preheated at 400°C for 30 minutes, and then heated for evaporation to obtain an inorganic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment is 5r / min, and the evaporation rate is controlled at
[0107] By transmission to the adjacent cavity, in 1×10 -3 Under a vacuum degree of 1.5 Pa, FAI powder and MAI powder were mixed at a weight ratio of FAI:MAI=8.85:1 and heated for evaporation to obtain an organic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment was 5 r / min, and the evaporation rate was controlled at
[0108] Then, according to the above parameters, the above inorganic salt and the above organic salt are cyclically evaporated in sequence, and the evaporation thicknesses are: 50nm inorganic salt evaporation layer, 145nm organic salt evaporation layer, 60nm inorganic salt evaporation layer, 200nm organic salt evaporation layer, 80nm inorganic salt evaporation layer, 200nm organic salt evaporation layer, 60nm inorganic salt evaporation layer, 145nm organic salt evaporation layer and 50nm inorganic salt evaporation layer. At this time, the sum of the thicknesses of the inorganic salt evaporation layers is 300nm, and a composite thin film is obtained.
[0109] Finally, the composite film was annealed at 1500°C for 10 min to obtain a perovskite film.
[0110] The perovskite film includes the following thicknesses, which are stacked in sequence: an inorganic salt vapor deposition layer of 50nm, an organic salt vapor deposition layer of 145nm, an inorganic salt vapor deposition layer of 60nm, an organic salt vapor deposition layer of 200nm, an inorganic salt vapor deposition layer of 80nm, an organic salt vapor deposition layer of 200nm, an inorganic salt vapor deposition layer of 60nm, an organic salt vapor deposition layer of 145nm, and an inorganic salt vapor deposition layer of 50nm. The total number of layers of the perovskite film is 9. The total number of layers of the inorganic salt vapor deposition layer is 5, and the total number of layers of the organic salt vapor deposition layer is 4. The chemical formula of the perovskite film is FA 0.8 Cs 0.1 MA 0.1PbI2Br, wherein the total thickness of the inorganic salt vapor-deposited layer is 300 nm, the total thickness of the organic salt vapor-deposited layer is 690 nm, and the total thickness of the perovskite film is 990 nm.
[0111] Among them, the evaporation area × evaporation thickness = coating volume, coating volume × coating density = coating weight. In the actual evaporation process, the raw materials used for evaporation are excessive, but the evaporation thickness can be precisely controlled. By controlling the evaporation thickness, the weight of a single layer of coating can be obtained, and then the number of layers can be coordinated to obtain the final perovskite film corresponding to the target chemical formula.
[0112] (5) Preparation of inorganic salt passivation layer: On the surface of the perovskite film, a LiF passivation layer with a thickness of 3 nm is obtained by evaporation.
[0113] (6) Preparation of electron transport layer: On the surface of the inorganic salt passivation layer, an electron transport layer with excellent electron extraction ability and energy band matching is prepared by evaporation. The material used is tin oxide, and its thickness is 20 nm.
[0114] (7) Preparation of electrode layer: On the surface of the electron transport layer, an electrode layer is prepared on the upper end of the electron transport layer by evaporation to draw out current. The material used is Ag and the thickness of the electrode layer is 100 nm.
[0115] The perovskite inverse cell comprises a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer which are sequentially stacked on the surface of a conductive glass bottom layer. In the perovskite film, the layer connected to the organic salt passivation layer is an inorganic salt vapor deposition layer.
[0116] Example 2
[0117] The method for preparing a perovskite solar cell provided in this embodiment comprises the following steps:
[0118] (1) Bottom layer cleaning: Place the bottom layer of the conductive glass in a cleaning machine for UV cleaning.
[0119] (2) Preparation of hole transport layer: On the cleaned conductive glass substrate, a hole transport layer with excellent hole extraction ability and energy band matching is prepared by evaporation. The material of the hole transport layer is FDT. The thickness of the hole transport layer is 40 nm.
[0120] (3) Preparation of organic salt passivation layer: On the surface of the hole transport layer, an organic salt passivation layer is prepared by evaporation, and the organic salt material used is p-fluorophenylethylamine iodine. The thickness of the organic salt passivation layer is 2 nm.
[0121] (4) Preparation of perovskite film: On the surface of the organic salt passivation layer, a 1×10 -4Under a vacuum degree of 1.5 Pa, PbI2 powder, PbBr2 powder, and CsI powder were placed in a crucible with a weight ratio of PbI2:PbBr2:CsI=5.02:7.06:1, preheated at 300°C for 60 minutes, and then heated for evaporation to obtain an inorganic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment is 5r / min, and the evaporation rate is controlled at
[0122] By transmission to the adjacent cavity, in 1×10 -4 Under a vacuum degree of 1.5 Pa, FAI powder and MAI powder were mixed at a weight ratio of FAI:MAI=8.85:1 and heated for evaporation to obtain an organic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment was 5 r / min, and the evaporation rate was controlled at
[0123] Then, according to the above parameters, the above-mentioned inorganic salt and the above-mentioned organic salt are evaporated in sequence in a cycle, and the evaporation thicknesses are: 20nm inorganic salt evaporation layer, 70nm organic salt evaporation layer, 40nm inorganic salt evaporation layer, 100nm organic salt evaporation layer, 40nm inorganic salt evaporation layer, 100nm organic salt evaporation layer, 50nm inorganic salt evaporation layer, 150nm organic salt evaporation layer, 50nm inorganic salt evaporation layer, 100nm organic salt evaporation layer, 40nm inorganic salt evaporation layer, 100nm inorganic salt evaporation layer, 40nm organic salt evaporation layer, 70nm inorganic salt evaporation layer and 20nm inorganic salt evaporation layer. At this time, the sum of the thicknesses of the inorganic salt evaporation layers is 300nm, and a composite thin film is obtained.
[0124] Finally, the composite film was annealed at 1200°C for 20 minutes to obtain a perovskite film.
[0125] The perovskite film includes the following thicknesses, which are stacked in sequence: an inorganic salt vapor deposition layer of 20nm, an organic salt vapor deposition layer of 70nm, an inorganic salt vapor deposition layer of 40nm, an organic salt vapor deposition layer of 100nm, an inorganic salt vapor deposition layer of 40nm, an organic salt vapor deposition layer of 100nm, an inorganic salt vapor deposition layer of 50nm, an organic salt vapor deposition layer of 150nm, an inorganic salt vapor deposition layer of 50nm, an organic salt vapor deposition layer of 100nm, an inorganic salt vapor deposition layer of 40nm, an organic salt vapor deposition layer of 100nm, an inorganic salt vapor deposition layer of 40nm, an organic salt vapor deposition layer of 70nm, and an inorganic salt vapor deposition layer of 20nm. The total number of layers of the perovskite film is 15. The total number of layers of the inorganic salt vapor deposition layer is 8, and the total number of layers of the organic salt vapor deposition layer is 7. The chemical formula of the perovskite film is FA 0.8 Cs 0.1 MA 0.1 PbI2Br, wherein the total thickness of the inorganic salt vapor-deposited layer is 300 nm, the total thickness of the organic salt vapor-deposited layer is 690 nm, and the total thickness of the perovskite film is 990 nm.
[0126] (5) Preparation of inorganic salt passivation layer: On the surface of the perovskite film, a LiF passivation layer with a thickness of 3 nm is obtained by evaporation.
[0127] (6) Preparation of electron transport layer: On the surface of the inorganic salt passivation layer, an electron transport layer with excellent electron extraction ability and energy band matching is prepared by atomic deposition. The material used is tin oxide, and its thickness is 50 nm.
[0128] (7) Preparation of electrode layer: On the surface of the electron transport layer, an electrode layer is prepared on the upper end of the electron transport layer by evaporation to draw out current. The material used is Ag and the thickness of the electrode layer is 150 nm.
[0129] The perovskite inverse cell comprises a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer which are sequentially stacked on the surface of a conductive glass bottom layer. In the perovskite film, the layer connected to the organic salt passivation layer is an inorganic salt vapor deposition layer.
[0130] Example 3
[0131] The method for preparing a perovskite solar cell provided in this embodiment comprises the following steps:
[0132] (1) Bottom layer cleaning: Place the bottom layer of the conductive glass in a cleaning machine for plasma cleaning.
[0133] (2) Preparation of hole transport layer: On the cleaned conductive glass substrate, a hole transport layer with excellent hole extraction ability and energy band matching is prepared by sputtering. The material of the hole transport layer is nickel oxide. The thickness of the hole transport layer is 60 nm.
[0134] (3) Preparation of organic salt passivation layer: On the surface of the hole transport layer, an organic salt passivation layer is prepared by evaporation, and the organic salt material used is tetra-tert-butylphenylammonium chloride. The thickness of the organic salt passivation layer is 5 nm.
[0135] (4) Preparation of perovskite film: On the surface of the organic salt passivation layer, a 1×10 -5 Under a vacuum degree of 1.5 Pa, PbI2 powder, PbBr2 powder, and CsI powder were placed in a crucible with a weight ratio of PbI2:PbBr2:CsI=5.02:7.06:1, preheated at 500°C for 10 minutes, and then heated for evaporation to obtain an inorganic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment is 5r / min, and the evaporation rate is controlled at
[0136] By transmission to the adjacent cavity, in 1×10 -5Under a vacuum degree of 1.5 Pa, FAI powder and MAI powder were mixed at a weight ratio of FAI:MAI=8.85:1 and heated for evaporation to obtain an organic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment was 5 r / min, and the evaporation rate was controlled at
[0137] Then, according to the above parameters, the above inorganic salt and the above organic salt are evaporated in a cycle in sequence, and the evaporation thickness is: inorganic salt evaporation layer 80nm, organic salt evaporation layer 345nm, inorganic salt evaporation layer 140nm, organic salt evaporation layer 345nm and inorganic salt evaporation layer 80nm. At this time, the sum of the thickness of each inorganic salt evaporation layer is 300nm, and a composite thin film is obtained.
[0138] Finally, the composite film was annealed at 1800°C for 10 min to obtain a perovskite film.
[0139] The perovskite film includes the following thicknesses, which are stacked in sequence: an inorganic salt vapor-deposited layer of 80 nm, an organic salt vapor-deposited layer of 345 nm, an inorganic salt vapor-deposited layer of 140 nm, an organic salt vapor-deposited layer of 345 nm, and an inorganic salt vapor-deposited layer of 80 nm. The total number of layers of the perovskite film is 5. The total number of layers of the inorganic salt vapor-deposited layer is 3, and the total number of layers of the organic salt vapor-deposited layer is 2. The chemical formula of the perovskite film is FA 0.8 Cs 0.1 MA 0.1 PbI2Br, wherein the total thickness of the inorganic salt vapor-deposited layer is 300 nm, the total thickness of the organic salt vapor-deposited layer is 690 nm, and the total thickness of the perovskite film is 990 nm.
[0140] (5) Preparation of inorganic salt passivation layer: On the surface of the perovskite film, a LiF passivation layer with a thickness of 3 nm is obtained by evaporation.
[0141] (6) Preparation of electron transport layer: On the surface of the inorganic salt passivation layer, an electron transport layer with excellent electron extraction ability and energy band matching is prepared by sputtering. The material used is C60, and its thickness is 80 nm.
[0142] (7) Preparation of electrode layer: On the surface of the electron transport layer, a layer of electrode is prepared on the upper end of the electron transport layer by magnetron sputtering to draw out current. The material used is Cu, and the thickness of the electrode layer is 200 nm.
[0143] The perovskite inverse cell comprises a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer which are sequentially stacked on the surface of a conductive glass bottom layer. In the perovskite film, the layer connected to the organic salt passivation layer is an inorganic salt vapor deposition layer.
[0144] Example 4
[0145] The preparation method of the perovskite solar cell provided in this embodiment is basically the same as that in embodiment 3, except that: in step (4), the thickness of each inorganic salt vapor deposition layer is 60nm, the total number of inorganic salt vapor deposition layers is 5 layers, the thickness of each organic salt vapor deposition layer is 138nm, and the total number of organic salt vapor deposition layers is 5 layers. That is, the total number of layers of the perovskite film is 10 layers. The structural formula of the perovskite film is FA 0.8 Cs 0.1 MA 0.1 PbI2Br, wherein the total thickness of the inorganic salt vapor-deposited layer is 400 nm, the total thickness of the organic salt vapor-deposited layer is 690 nm, and the total thickness of the perovskite film is 990 nm.
[0146] Example 5
[0147] The preparation method of the perovskite solar cell provided in this embodiment is basically the same as that in embodiment 1, except that: in step (4), the chemical formula of the perovskite film is replaced by FA 0.7 Cs 0.1 MA 0.2 PbI 2.5 Br 0.5 , that is, in step (4), the weight ratio of PbI2:PbBr2:CsI is replaced with 7.53:3.53:1, and the weight ratio of FAI:MAI is replaced with 3.87:1.
[0148] Example 6
[0149] The preparation method of the perovskite solar cell provided in this embodiment is basically the same as that in embodiment 1, except that: in step (4), the chemical formula of the perovskite film is replaced by FA 0.9 MA 0.1 PbI3, that is, in step (4), PbI2 powder, PbBr2 powder, and CsI powder are placed in a crucible with a weight ratio of PbI2:PbBr2:CsI=10:0:0 (that is, only PbI2 is added), and the weight ratio of FAI:MAI is replaced with 9.96:1.
[0150] Comparative Example 1
[0151] The preparation method of the perovskite solar cell provided in this comparative example is basically the same as that in Example 1, except that: in step (4), only one layer of inorganic salt and one layer of organic salt are evaporated, that is, the number of layers of the inorganic salt evaporated layer and the organic salt evaporated layer are both 1, and the thickness of the inorganic salt evaporated layer is 300nm, and the thickness of the organic salt evaporated layer is 690nm.
[0152] Comparative Example 2
[0153] The preparation method of the perovskite solar cell provided in this comparative example is basically the same as that in Example 1, except that: in step (4), the chemical formula of the perovskite film is replaced by FA 0.1 Cs 0.8 MA 0.1 PbIBr2.
[0154] (1) Bottom layer cleaning: Place the bottom layer of the conductive glass in a cleaning machine for UV cleaning.
[0155] (2) Preparation of hole transport layer: On the cleaned conductive glass substrate, a hole transport layer with excellent hole extraction ability and energy band matching is prepared by evaporation. The material of the hole transport layer is cuprous thiocyanate. The thickness of the hole transport layer is 20 nm.
[0156] (3) Preparation of organic salt passivation layer: On the surface of the hole transport layer, an organic salt passivation layer is prepared by evaporation, and the organic salt material used is tetrabutylammonium bromide. The thickness of the organic salt passivation layer is 3 nm.
[0157] (4) Preparation of perovskite film: On the surface of the organic salt passivation layer, a 1×10 -3 Under a vacuum degree of 1.5 Pa, PbBr2 powder and CsI powder were placed in a crucible with a weight ratio of PbBr2:CsI=1.76:1, preheated at 400°C for 30 minutes, and then heated for evaporation to obtain an inorganic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment was 5r / min, and the evaporation rate was controlled at
[0158] By transmission to the adjacent cavity, in 1×10 -3 Under a vacuum degree of 1.5 Pa, FAI powder and MAI powder were mixed at a weight ratio of FAI:MAI=1:1 and heated for evaporation to obtain an organic salt evaporation layer. The substrate stage rotation speed of the evaporation equipment was 5 r / min, and the evaporation rate was controlled at
[0159] Then, according to the above parameters, the above inorganic salt and the above organic salt are cyclically evaporated in sequence, and the evaporation thicknesses are: 50nm inorganic salt evaporation layer, 100nm organic salt evaporation layer, 60nm inorganic salt evaporation layer, 200nm organic salt evaporation layer, 80nm inorganic salt evaporation layer, 200nm organic salt evaporation layer, 60nm inorganic salt evaporation layer, 137nm organic salt evaporation layer and 50nm inorganic salt evaporation layer. At this time, the sum of the thicknesses of the inorganic salt evaporation layers is 300nm, and a composite thin film is obtained.
[0160] Finally, the composite film was annealed at 1500°C for 10 min to obtain a perovskite film.
[0161] The perovskite film includes the following thicknesses, which are stacked in sequence: an inorganic salt vapor deposition layer of 50nm, an organic salt vapor deposition layer of 100nm, an inorganic salt vapor deposition layer of 60nm, an organic salt vapor deposition layer of 200nm, an inorganic salt vapor deposition layer of 80nm, an organic salt vapor deposition layer of 200nm, an inorganic salt vapor deposition layer of 60nm, an organic salt vapor deposition layer of 137nm, and an inorganic salt vapor deposition layer of 50nm. The total number of layers of the perovskite film is 9. The total number of layers of the inorganic salt vapor deposition layer is 5, and the total number of layers of the organic salt vapor deposition layer is 4. The chemical formula of the perovskite film is FA 0.1 Cs 0.8 MA 0.1 PbIBr2, wherein the total thickness of the inorganic salt evaporated layer is 300 mm, the total thickness of the organic salt evaporated layer is 637 mm, and the total thickness of the perovskite film is 937 nm.
[0162] (5) Preparation of inorganic salt passivation layer: On the surface of the perovskite film, a LiF passivation layer with a thickness of 3 nm is obtained by evaporation.
[0163] (6) Preparation of electron transport layer: On the surface of the inorganic salt passivation layer, an electron transport layer with excellent electron extraction ability and energy band matching is prepared by evaporation. The material used is tin oxide, and its thickness is 20 nm.
[0164] (7) Preparation of electrode layer: On the surface of the electron transport layer, an electrode layer is prepared on the upper end of the electron transport layer by evaporation to draw out current. The material used is Ag and the thickness of the electrode layer is 100 nm.
[0165] The perovskite inverse cell comprises a hole transport layer, an organic salt passivation layer, a perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer which are sequentially stacked on the surface of a conductive glass bottom layer. In the perovskite film, the layer connected to the organic salt passivation layer is an inorganic salt vapor deposition layer.
[0166] Comparative Example 3
[0167] The preparation method of the perovskite solar cell provided in this comparative example is basically the same as that of Example 1, except that the organic salt passivation layer is not evaporated.
[0168] Comparative Example 4
[0169] The preparation method of the perovskite solar cell provided in this comparative example is basically the same as that of Example 1, except that the inorganic salt passivation layer is not evaporated.
[0170] Experimental example
[0171] The effective area of the perovskite solar cell devices obtained in each embodiment and each comparative example is 4 mm 2 , using a xenon lamp solar simulator, the test light source intensity is AM1.5G, 100mW / cm2 The JV performance curves of the perovskite solar cells prepared in each embodiment and each comparative example were tested under light, and the following parameters were obtained: open circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), and photoelectric conversion efficiency (PCE). The results are shown in Table 1.
[0172] Table 1 Performance test results of various perovskite solar cells
[0173]
[0174]
[0175] It can be seen from Table 1 that, in general, the efficiency of the perovskite solar cells prepared in the embodiments is excellent, while the efficiency of the comparative examples is poor.
[0176] Specifically, by comparing Example 3, Example 4 and Comparative Example 1, it can be seen that the thickness of the inorganic salt vapor-deposited layer and the number of vapor-deposited layers, the thickness of the organic salt vapor-deposited layer and the number of vapor-deposited layers will have a certain impact on the perovskite crystallization conversion rate, among which the perovskite crystallization conversion rate of Example 1 is better, and its photoelectric conversion rate is the highest. In Comparative Example 1, only one layer of inorganic salt and one layer of organic salt are vapor-deposited, which will lead to a decrease in open circuit voltage, short circuit current density, fill factor and photoelectric conversion rate. This is because the organic salt cannot fully diffuse in the inorganic salt layer and cannot achieve complete conversion of perovskite.
[0177] By comparing Example 1, Example 5, Example 6 and Comparative Example 2, it can be seen that the chemical composition of the perovskite film will have a certain impact on the device efficiency, among which the perovskite crystallization conversion rate of Example 1 is better and its photoelectric conversion rate is the highest. The chemical composition of the perovskite film in Comparative Example 2 is not suitable, which will lead to a significant decrease in open circuit voltage, short circuit current density, fill factor and photoelectric conversion rate. This is because the proportion of organic salt is too small, which is not conducive to stabilizing the α phase, and the film quality of the perovskite is affected, so the photoelectric conversion rate is low.
[0178] By comparing Example 1 and Comparative Example 3, it can be seen that the lack of an organic salt passivation layer evaporated in Comparative Example 3 will result in a significant decrease in open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency. This is because the organic salt passivation layer can reduce surface defects and increase the carrier mobility of the perovskite film, thereby improving the photoelectric conversion efficiency.
[0179] By comparing Example 1 and Comparative Example 4, it can be seen that the inorganic salt passivation layer is not evaporated in Comparative Example 4, which will lead to a significant decrease in open circuit voltage, short circuit current density, fill factor and photoelectric conversion rate. This is because there are a large number of defects on the interface between the electron transport layer and the perovskite absorption layer. These defects are prone to cause the performance of the crystalline silicon / perovskite laminated solar cell to be low and unstable. The inorganic salt passivation layer can interact with the surface of the perovskite film, which can effectively fill the grain boundary defects on the perovskite surface, reduce the surface roughness, and optimize the surface morphology, thereby reducing the recombination of carriers at the interface and enhancing the transmission of carriers. If the inorganic salt passivation layer is missing, the photoelectric conversion rate of the device will be reduced.
[0180] Further, Figure 2 This is a SEM cross-sectional view of the perovskite film obtained in Example 1 provided by the present invention; Figure 3 This is a SEM surface morphology of the perovskite film obtained in Example 1 provided by the present invention. Figure 2 It can be seen that the perovskite particles reach the micron level and the perovskite crystals are in good condition; Figure 3 It can be seen that the uniformity of the perovskite film is good.
[0181] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A perovskite film, characterized in that: It comprises an inorganic salt vapor deposition layer and an organic salt vapor deposition layer which are alternately stacked in a cycle in sequence; wherein the inorganic salt vapor deposition layer comprises at least three layers, and the organic salt vapor deposition layer comprises at least two layers; The thickness of each inorganic salt vapor-deposited layer is 10 to 300 nm; The thickness of each organic salt vapor-deposited layer is 10 to 400 nm; The general formula of the perovskite film is FA 1-y-z Cs y MA z PbI 3-x Br x , where 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, 0≤y+z≤0.
5.
2. The perovskite film according to claim 1, characterized in that: At least one of the following conditions is met: (1) The thickness of each inorganic salt vapor-deposited layer is 20 to 200 nm; (2) The thickness of each organic salt vapor-deposited layer is 20 to 400 nm; (3) The thickness ratio of the adjacent inorganic salt vapor-deposited layer to the organic salt vapor-deposited layer is 0.1 to 5:1; (4) The sum of the thicknesses of the inorganic salt vapor-deposited layers is 60 to 500 nm; (5) The inorganic salt vapor-deposited layer comprises at least five layers; (6) The organic salt vapor-deposited layer comprises at least four layers; (7)0≤x≤1; (8)0≤y≤0.2; (9)0.1≤z≤0.2; (10)0.1≤y+z≤0.4; (11) The chemical formula of the perovskite film includes FA 0.9 MA 0.1 PbI2Br、FA 0.8 Cs 0.1 MA 0.1 PbI2Br、FA 0.8 Cs 0.1 MA 0.1 PbI 2.5 Br 0.5 , FA 0.7 Cs 0.1 MA 0.2 PbI 2.5 Br 0.5 , FA 0.7 Cs 0.1 MA 0.2 PbI2Br and FA 0.9 MA 0.1 PbI3.
3. The method for preparing a perovskite thin film according to any one of claims 1 to 2, characterized in that: The steps include: According to FA 1-y-z Cs y MA z PbI 3-x Br x , 0≤x≤1.5, 0≤y≤0.5, 0≤z≤0.5, 0≤y+z≤0.5, sequentially cyclically depositing an inorganic salt material and an organic salt material on the surface of the bottom layer, wherein the inorganic salt material is deposited in at least three layers and the organic salt material is deposited in at least two layers, and then annealing is performed; The inorganic salt material is selected from at least one of PbI2, PbBr2, CsI and CsBr, the organic salt material is selected from at least one of FABr, FAI, MABr and MAI, and the inorganic salt material contains Pb element, the organic salt material contains FA group, and the inorganic salt material and / or the organic salt material contain I element.
4. The method for preparing a perovskite thin film according to claim 3, characterized in that: At least one of the following conditions is met: (1) The method for evaporating the inorganic salt material includes a preheating method; the steps of evaporating the inorganic salt material using the preheating method are as follows: weighing each raw material according to the target chemical formula ratio and placing it in a crucible, and -3 Pa~1×10 -5 Pa, preheat at 300-500°C for 10-60 min, and then perform heating evaporation; (2) The method for evaporating the inorganic salt material includes a single crystal method; the steps of evaporating the inorganic salt material using the single crystal method are as follows: mixing the raw materials according to the target chemical formula ratio and preparing a single crystal material by melting, and then heating and evaporating the single crystal material as a material; (3) The method of vapor-depositing the organic salt material comprises: mixing the raw materials uniformly according to the target chemical formula ratio, and then heating and vapor-depositing; or, heating the raw materials separately, mixing and vapor-depositing; (4) The vacuum degree during the evaporation of the inorganic salt material is ≤1×10 -3 Pa; (5) The evaporation rate of the inorganic salt material during the evaporation is (6) When the inorganic salt material is evaporated, the rotation speed of the substrate stage of the evaporation equipment is 3 to 20 r / min; (7) The vacuum degree during the evaporation of the organic salt material is ≤1×10 -2 Pa; (8) The evaporation rate of the organic salt material during the evaporation is: (9) When the organic salt material is evaporated, the rotation speed of the substrate stage of the evaporation equipment is 3 to 20 r / min; (10) The temperature of the annealing treatment is 1000-2000° C.; (11) The holding time of the annealing treatment is 10 to 60 minutes; (12) The bottom layer includes a substrate and an electron transport layer disposed on the surface of the substrate; (13) The bottom layer includes a substrate, and an electron transport layer and an inorganic salt passivation layer sequentially stacked on the surface of the substrate; (14) The bottom layer includes a substrate and a hole transport layer disposed on the surface of the substrate; (15) The base layer includes a substrate, and a hole transport layer and an organic salt passivation layer sequentially stacked on the surface of the substrate.
5. A perovskite solar cell, characterized in that: Comprising the perovskite film as claimed in claim 1.
6. The perovskite solar cell according to claim 5, characterized in that: The perovskite solar cells include single perovskite cells, stacked perovskite cells, regular perovskite cells and trans-perovskite cells; Alternatively, the perovskite solar cell includes a substrate, and a hole transport layer, an organic salt passivation layer, the perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer which are sequentially stacked on the surface of the substrate.
7. The perovskite solar cell according to claim 6, characterized in that: At least one of the following conditions is met: (1) The hole transport layer comprises at least one of nickel oxide, cuprous thiocyanate and oligomeric PACz; (2) The thickness of the hole transport layer is 10 to 100 nm; (3) the organic salt passivation layer comprises at least one of tetrabutylammonium bromide, tetrabutylammonium iodide, methylammonium bromide, methylammonium chloride, ethylammonium chloride, phenethylammonium iodide, p-fluorophenethylammonium iodide, methylammonium iodide, phenethylammonium chloride, phenethylammonium bromide, tetra-tert-butylphenylammonium chloride, butylammonium bromide, isopropylammonium bromide, octylammonium iodide, benzylammonium chloride, tetrafluorobenzylammonium iodide, phenylpropylammonium iodide and tetrafluorophenethylammonium bromide; (4) The thickness of the organic salt passivation layer is 1 to 5 nm; (5) The inorganic salt passivation layer includes LiF; (6) The thickness of the inorganic salt passivation layer is 1 to 5 nm; (7) The electron transport layer includes at least one of titanium dioxide, zinc oxide, C60 and tin oxide; (8) The thickness of the electron transport layer is 10 to 100 nm; (9) The electrode layer includes at least one of copper and silver; (10) The thickness of the electrode layer is 50 to 200 nm.
8. The method for preparing a perovskite solar cell according to any one of claims 5 to 7, characterized in that: The fully dry method is adopted to form various functional layers on the substrate to obtain the perovskite solar cell; wherein the dry process of the fully dry method at least includes a vapor deposition method.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: At least one of the following conditions is met: (1) The dry process of the all-dry method further includes at least one of a sputtering method and an atomic deposition method; (2) preparing a hole transport layer, an organic salt passivation layer, the perovskite film, an inorganic salt passivation layer, an electron transport layer and an electrode layer by a fully dry method; (3) The substrate comprises conductive glass; (4) The substrate is cleaned by at least one of plasma cleaning and ultraviolet cleaning.
10. An electrical device, characterized in that: Comprising the perovskite solar cell as claimed in claim 5.